IMPLEMENTASI PENGELOLAAN KEUAGAN NEGARA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI APBN 2017-2021) - Luluk Novita; Pardiman M Pardiman M; Ridwan Basalamah (Reflektika, 2022)
Management of the state budget by implementing fiscal Policy; fiscal Policy is a large-scale economic policy that is also implemented through the State Budget. The modern concept of the State Budget (APBN) uses the idea of Baitul Mal or a balanced budget, which in Islam is used to spend the budget even if it is in debt but should not and is not recommended in Islam. The purpose of this article is to analyze the country's financial management after the enactment of law number 17 of 2003. The results of the study stated that in managing state finances which are expected to create a stable economy for the welfare of the community, management must be balanced between expenditure and income and must be balanced with the Islamic economic system so that the country's economy can grow well and avoid deficits.